Desenvolvimento de metodologias eletroanalíticas para o monitoramento de glifosato em águas de rio - Prezilius, Ana Carolina Miranda (2021)
Glyphosate is a post-emergent herbicide, belonging to the chemical group of replaced glycines, classified as non-selective and systemic. These characteristics make glyphosate one of the most potent herbicides in existence and, for this reason, one of the most consumed in the world. However, its excessive and indiscriminate use makes the environment susceptible to contamination, especially aquatic matrices such as river water. Therefore, it is necessary to develop analytical methodologies that allow the determination of this contaminant in a simple, fast, sensitive way and that comply with current legislation. In this context, the present work developed electroanalytical methodologies using the voltammetric techniques (chronoamperometry and square wave voltammetry, SWV), associated with gold screen-printed electrodes and solid copper electrode for the determination of the herbicide glyphosate in water samples from the Timbuí River, one of the main tributaries of the Reis Magos River basin and which currently assists in the water supply of Greater Vitória. We start from a technique already described in the literature (chronoamperometry) and alternatively employ a faster, selective e more sensitive technique (SWV) using screen-printed gold electrode (low temperature curing ink) (SPGE-BT). For the chronoamperometry, a potential of 0.75 V for 50 s in a linear range from 0.5 to 10 µmol L−¹ was applied. The main SWV operating parameters were optimized (step potential (7 mV), modulation amplitude (18 mV) and frequency (8 Hz)) using univariate experiments. SWV methodology presented a limit of detection of 0.6676 ± 0.0070 μmol L−¹ and a sensibility of 0.0646 μA mol−¹ L for glyphosate in 0.1 mol L−¹ sodium acetate buffer. The SWV performance characteristics were obtained by applying a linear range from 1.0 to 8.0 µmol L−¹ . The recovery test in a fortified river water sample with glyphosate showed values between 91,5 and 101%, indicating that there is no matrix effect. These results reinforce the possibility of applying the proposed method in a practical and fast way (four times faster than chronoamperometry), without the need for significant amounts of sample and promoting more sustainable chemistry.